Newsday, May 16, 1978 (1978)
[00:00:02] Micronesian - Japanese relations with Carly Sanders [00:00:39] Acting lessons for lawyers with Carly Sanders [00:01:25] 91 Newswatch Promo [00:02:27] 91 Newswatch Promo [00:02:42] Kevin Riggs with a summary of the upcoming stories [00:03:07] VA Hospital Volunteers / Voluntary Service Program [00:04:06] Local news with Kevin Riggs- Arroyo Grande children Tammy and Scott Sage rescued with new ambulances [00:04:42] Grover City youth drowns in Lopez Lake spillway [00:06:09] Wayne Leonard to speak at advertising training program for Cal Poly [00:06:52] Campus news continues [00:07:19] ASI Election results - John Griffin, Scott Walton, Ann Clendennen, Larry Robinson [00:08:10] Speech/Communication building construction continues [00:08:33] Population Institute surrealist PSA [00:09:42] World News [00:10:17] Senate votes to allow jet fighters to be sold to Middle East [00:10:44] Chilean ship Esmeralda on good-will visit to San Francisco [00:11:56] Report on Leon Panetta with Dave Kerley [00:14:19] Weather [00:14:59] U.S. Travel Service traveling with pets PSA [00:16:19] Vivi Sanomond on solar energy [00:17:28] PSA on obesity [00:18:36] Kevin Riggs continues national news [00:19:31] Report on Rhodesian refugees [00:19:58] Tape damage increases, ceased recording